Font Size: Small Medium Large Economic Sector Portfolio Optimization in the Commercial and Retail Segments - Sulistyorini, Diah Diana; Hartoyo, Sri; Andati, Trias (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
Credit disbursement is an investment decision in the banking business. Therefore, the concept of "high risk high return" becomes the focus of banks in managing credit. One of the effort of these banks to manage risk and enhancing/ increasing returns is forming their portfolio. This research was conducted in one of the state banks in Indonesia, which has the goal of increasing lending in the retail and commercial segments. Single Index Model is used to find the optimal composition of the economic sector. This model recommends economic sectors into the portfolio on the basis of Excess Return to Beta, which represents the difference between the rates of return in the form of interest income with a risk-free asset returns, divided by beta sectors of the economy itself. The results showed that the return portfolio can be improved and the risks derived using that approach. Banking business purpose is the return and growth so that the portfolio optimization needs to be supported with other parameters when the economic sectors that are not recommended put in a portfolio. Analysis of the performance of RAROC is a performance metric that of performance that computes net profit after adjusting for potential losses than capital allocation, can be used to help the formation of portfolios that received the return and risk are still in line with expectations.